1994
DOI: 10.2105/ajph.84.11.1836
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of tuberculosis among North Carolina migrant farmworkers, 1991.

Abstract: All locatable subjects (n = 94) for whom tuberculosis prevalence had been determined in an earlier study were tested with purified protein derivative (PPD) and control antigens, sputum sampling, and chest x-rays. Of the 46 who had been tuberculin negative (confirmed with control antigens) 3 years earlier, 2 had developed active tuberculosis in the interim and 14 (30%) were tuberculin positive. All had been engaged continuously in migrant farmwork. Lack of access to health care, an institutional feature of migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A 1988 study of 435 North Carolina migrant farm workers found a 31% prevalence for tuberculin reactivity [Simmons et al, 1989]. Ciesielski et al [ , 1994 studied migrant farm workers in migrant-farm-labor camps in North Carolina in 1991. Reactivity was present in 30% of Hispanic workers, compared with 44% of African-Americans and 76% of Haitians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1988 study of 435 North Carolina migrant farm workers found a 31% prevalence for tuberculin reactivity [Simmons et al, 1989]. Ciesielski et al [ , 1994 studied migrant farm workers in migrant-farm-labor camps in North Carolina in 1991. Reactivity was present in 30% of Hispanic workers, compared with 44% of African-Americans and 76% of Haitians.…”
Section: Discussionmentioning
confidence: 99%
“…Migrant farm workers in California are predominantly Hispanic and belong to the western migrant stream extending from southern California and Arizona into Oregon and Washington [Mobed et al, 1992]. Despite the size and importance of the migrant-farm-worker population in California, most epidemiologic studies of tuberculosis among migrant farm workers have been conducted in the midwestern and eastern migrant streams [CDC, 1986;Ciesielski et al, 1994Garcia et al, 1996;Jacobson et al, 1987;Simmons et al, 1989;Villarino et al, 1994]. The eastern migrant stream is ethnically heterogenous, comprising Hispanics, non-Hispanic whites, Caribbean peoples, and other groups.…”
Section: Introductionmentioning
confidence: 99%
“…In North America, employers often provide overcrowded housing for farm workers, which in creases the risk of transmission of infectious diseases such as tuberculosis. 23,24 Poor sanitation and inadequate means to refrigerate and heat food, along with insufficient toilet and handwashing facilities at worksites, may also heighten the risk of farm workers developing and spreading enteric, foodand waterborne diseases. 25,26 The implications for Canada's food system, given the increasing numbers of migrant workers em ployed in agriculture, meat processing and food services, is a major public health concern.…”
Section: Migration and Public Healthmentioning
confidence: 99%
“…Follow-up work in the North Carolina study for the 46 persons who initially exhibited negative PPD results showed that 2 had contracted active tuberculosis and 14 were PPD positive (19). High levels of positive PPD cases have been found in other studies as well: 44% in a sample in which 5% were also HIV-positive (74), suggesting that reduced immunity is an important factor in the increased prevalence of tuberculosis; and 30% in a sample of migrant farm workers who were recruited to participate in a health education program (53).…”
Section: The Control Of Infectious Diseasesmentioning
confidence: 99%